PELAKSANAAN TEKNIS PETERNAKAN DAN SITE PLANE UPTD PEMBIBITAN TERNAK UNGGUL DAN HIJAUAN PAKAN TERNAK DINAS PERKEBUNAN DAN PETERNAKAN KABUPATEN PELALAWAN - Hendri Siregar (SUNGKAI, 2023)
Livestock development is an integral part of agricultural and national development. Livestock development as an agricultural sub-sector has an important role in human life. This is related to the readiness of the livestock sub-sector in terms of providing animal food for the community. The aim of developing the livestock sub-sector is to increase income, expand employment opportunities, increase population and production as well as improve people's nutrition. In order to fulfill the community's nutrition sourced from animal protein, the priority for livestock development policies is directed to livestock business commodities that are supported by the potential of the region, so that its development will be supported by the availability of existing potential. The research was carried out in 2022 at the UPTD of Superior Livestock Breeding (PTU) and Forage Animal Feed (HPT) of the Plantation and Livestock Service Office of Pelalawan Regency. Based on the results of the technical/research reports that have been carried out, it can be concluded as follows: The condition of the technical implementation of animal husbandry in the existing (existing) UPTD of Superior Cattle Breeding and Forage Cattle Fodder of the Livestock Service Office of Pelalawan Regency: Viewed from the technical aspect of seed management. Livestock that has been developed has the potential to produce quality calves, Feeding using palm oil waste (cake and solid) and tofu dregs can reduce production costs, Rearing with semi-intensive and extensive term patterns can improve livestock health and reduce production costs, Services Reproductive techniques through Artificial Insemination (AI) will produce quality calves. Health services by implementing Biosecurity aspects will reduce livestock morbidity and mortality.